2021
DOI: 10.1186/s12879-021-06325-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and development of Sepsis in Klebsiella pneumoniae infected liver abscess patients: a retrospective analysis of 135 cases

Abstract: Background Klebsiella pneumoniae is a primary pathogen of pyogenic liver abscess (PLA). However, little data are available on combination with sepsis. In this study, we aimed to evaluate the clinical characteristics and prognostic differences of PLA patients with sepsis. Methods This retrospective cohort study was conducted to investigate 135 patients with confirmed Klebsiella pneumoniae-caused liver abscesses (KPLA) from a tertiary teaching hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 25 publications
2
19
0
Order By: Relevance
“…The major abnormalities of KLA in the laboratory were increased CRP and liver dysfunction. 32,33 It was also demonstrated in this investigation that the levels of CRP in diabetic-KLA patients were higher, which suggested a more severe infection. Sepsis is a lethal organ dysfunction caused by a dysregulated host response to an infection.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The major abnormalities of KLA in the laboratory were increased CRP and liver dysfunction. 32,33 It was also demonstrated in this investigation that the levels of CRP in diabetic-KLA patients were higher, which suggested a more severe infection. Sepsis is a lethal organ dysfunction caused by a dysregulated host response to an infection.…”
Section: Discussionsupporting
confidence: 61%
“…Septic-KLA patients had an increased risk of chronic metastatic complications and prolonged hospital stays. 33 The results from this research indicated that the incidence of sepsis was higher and the hospital stays were longer in KLA with diabetes. In this study, the virulence genes and capsular serotypes were detected by PCR.…”
Section: Discussionmentioning
confidence: 71%
“…All authors report Klebsiella pneumoniae and E. coli as the most common bacteria cultured in pus from PLA [ 1 , 24 , 27 , 28 , 31 , 34 ], with E. coli being more frequently associated with biliary diseases [ 1 , 23 , 31 ] and diabetes mellitus [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicated that men are more likely to develop hvKP infection than women (72% vs 28%), and the average age of patients was 61 years, which is consistent with previous studies. 11 Diabetes is generally considered to be a significant risk factor for acquiring a hvKP infection, but not cKP infection. 12 , 13 The reason for this may be that increased serum glucose levels can increase capsule production.…”
Section: Discussionmentioning
confidence: 99%